Air movement and temperature regime in large stacked apple bins during the initial phases of cold storage - Tuany Gabriela Hoffmann; Poonam Bidgar; Jincheng Yu; Daniel Alexandre Neuwald; Reiner Jedermann; Manfred Linke; Pramod Mahajan (Biosystems Engineering, 2026)

Heated debate: Is the seasonal polyphenism of the map butterfly Araschnia levana driven by thermoregulation? - Daniel Linke; Jan Okrouhlik; Alena Sucháčková Bartoňová; Leonardo Ré Jorge; Pável Matos-Maraví; Irena Kleckova (Journal of Thermal Biology, 2026)

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Challenges and future perspectives in postharvest cold storage: technological review on sustainable and efficient cold storage of fresh produce - Tuany Gabriela Hoffmann; Carolina Krebs de Souza; Akshay D. Sonawane; Ulrike Praeger; Felix Büchele; Daniel Alexandre Neuwald; Reiner Jedermann; Manfred Linke; Barbara Sturm; Pramod V. Mahajan (Food Research International, 2025)

Quantifying the success of prey crypsis, aposematism, and evasiveness in avoiding predator attack - Daniel Linke; Jacqueline Hernandez Mejia; Valery N. P. Eche Navarro; Prapti Gohil; César Ramírez García; Letty Salinas; Marianne Elias; Pável Matos‐Maraví (Ecology, 2025)
Antipredator defenses typically act at distinct stages of the predation sequence—encounter, identification, approach, and subjugation. However, their effectiveness has rarely been quantified and compared simultaneously in wild predator–prey systems. We conducted a study in Peru, where we installed aviaries at two localities and recorded the responses of wild avian predators to three types of antipredator defenses—crypsis, aposematism, and evasiveness—expressed by three butterfly prey types. The study included both immature and adult birds from forest and urban environments, representing the present community of insectivorous birds. We tested the theoretical expectations that cryptic butterflies (Nymphalidae: Euptychiina) were rarely detected, aposematic Heliconius (Nymphalidae: Heliconiinae) were often sighted but seldom attacked, and evasive Spicauda (Hesperiidae: Eudaminae) were frequently detected and attacked but evaded capture at higher rates. Despite these distinct defensive strategies, mortality rates among prey types were largely similar, but predator life stage strongly influenced defense effectiveness, with immature birds tending to attack Heliconius more frequently. Additionally, predator family influenced predation patterns, with more skilled insectivores (e.g., Vireonidae) showing higher capture success against defended prey. These findings illuminate the evolutionary pressures that shape predator behavior and prey defenses in tropical ecosystems. The similar mortality rates underscore the adaptive value of these defenses, which collectively distribute the total predation pressure across prey species.

Heat transfer in large bins during the apples cool-down process - Tuany Gabriela Hoffmann; Manfred Linke; Ulrike Praeger; Akshay D. Sonawane; Felix Büchele; Daniel Alexandre Neuwald; Reiner Jedermann; Barbara Sturm; Pramod V. Mahajan (International Journal of Refrigeration, 2025)

Thermoregulatory ability and mechanism do not differ consistently between neotropical and temperate butterflies - Benita C. Laird‐Hopkins; Esme Ashe‐Jepson; Yves Basset; Stephany Arizala Cobo; Lucy Eberhardt; Inga Freiberga; Josh Hellon; Gwen E. Hitchcock; Irena Kleckova; Daniel Linke; Greg P. A. Lamarre; Alex McFarlane; et al. (Global Change Biology, 2023)
Climate change is a major threat to species worldwide, yet it remains uncertain whether tropical or temperate species are more vulnerable to changing temperatures. To further our understanding of this, we used a standardised field protocol to (1) study the buffering ability (ability to regulate body temperature relative to surrounding air temperature) of neotropical (Panama) and temperate (the United Kingdom, Czech Republic and Austria) butterflies at the assemblage and family level, (2) determine if any differences in buffering ability were driven by morphological characteristics and (3) used ecologically relevant temperature measurements to investigate how butterflies use microclimates and behaviour to thermoregulate. We hypothesised that temperate butterflies would be better at buffering than neotropical butterflies as temperate species naturally experience a wider range of temperatures than their tropical counterparts. Contrary to our hypothesis, at the assemblage level, neotropical species (especially Nymphalidae) were better at buffering than temperate species, driven primarily by neotropical individuals cooling themselves more at higher air temperatures. Morphology was the main driver of differences in buffering ability between neotropical and temperate species as opposed to the thermal environment butterflies experienced. Temperate butterflies used postural thermoregulation to raise their body temperature more than neotropical butterflies, probably as an adaptation to temperate climates, but the selection of microclimates did not differ between regions. Our findings demonstrate that butterfly species have unique thermoregulatory strategies driven by behaviour and morphology, and that neotropical species are not likely to be more inherently vulnerable to warming than temperate species.

Active movement to coarse grained sediments by globally endangered freshwater pearl mussels (Margaritifera margaritifera) - Felix Eissenhauer; Felix Grunicke; Annekatrin Wagner; Daniel Linke; David Kneis; Markus Weitere; Thomas U. Berendonk (Hydrobiologia, 2023)
The freshwater pearl mussel Margaritifera margaritifera is an endangered bivalve which is usually regarded as sedentary, although individual movement has been observed both vertically and horizontally. Little is known about the causes and rates of mussel movement. The objective of this study was to test the effect of microhabitat characteristics on the horizontal movement distance and rates of freshwater pearl mussels. A total of 120 mussels (length range 40–59 mm) were marked individually with passive integrated transponder tags, placed in stream microhabitats differing in their sediment composition and monitored biweekly over a period of 10 weeks. Mussels situated in sand-dominated habitats had a significantly higher mean movement rate (3.2 ± 4.2 cm/day, mean ± SD) than mussels situated in gravel-dominated (1.9 ± 2.7 cm/day) or stone-dominated habitats (1.8 ± 3.2 cm/day). The direction of the movements appeared random; however, an emigration from sandy habitats was observed, probably to avoid dislodgment from these hydraulically unstable habitats. This study demonstrates that freshwater pearl mussels can actively emigrate from unsuitable microhabitats. Once suitable streams with respect to physical, chemical, and biological quality were identified, it is therefore only necessary to identify suitable mesohabitats (area of 10–30 m 2 ) when reintroducing or relocating mussels.

Bewegungszeit, Belastungsintensität und Bewegungsumfang im Sportunterricht - Jennifer Breithecker; David Jaitner; Julia Lohmann; Daniel Linke; Malte Siegle; Martin Lames; Hans Peter Brandl-Bredenbeck (German Journal of Exercise and Sport Research, 2021)
Zusammenfassung Untersuchungen zu Bewegungsanteilen im Sportunterricht unter Verwendung objektiver Verfahren sind in Deutschland selten. Sie sind jedoch sowohl aus gesundheits- und trainingswissenschaftlicher als auch aus sportpädagogischer Perspektive von Interesse, um Schulsportwirklichkeit systematisch analysieren zu können. Der vorliegende Beitrag untersucht Bewegungszeit (Minuten), Belastungsintensität (Herzschläge pro Minute) und Bewegungsumfang (Meter pro Minute) im Sportunterricht am Beispiel des Unterrichtsinhalts Fußball. Im Zentrum steht die Frage, ob sich Unterschiede für die Unterrichtsdauer (Einzelstunde/Doppelstunde), das Setting (indoor/outdoor) und das Geschlecht zeigen. Insgesamt nahmen 356 Schüler*innen (247 männlich, 109 weiblich) von der fünften bis zur zehnten Jahrgangsstufe ( M Alter = 12,4 Jahre) eines Gymnasiums in Bayern an der Untersuchung teil. Zum Einsatz kamen standardisierte Beobachtungsprotokolle, Herzfrequenzmesser und ein Trackingsystem (Local Position Measurement System [LPM-System]). Die Ergebnisse zeigten, dass die relative Bewegungszeit, die Belastungsintensität und der Bewegungsumfang in Einzelstunden am höchsten waren. Die relative Bewegungszeit war outdoor etwas höher als indoor. Die durchschnittliche Herzfrequenz unterschied sich nicht nach Setting und Geschlecht. Jungen erzielten einen höheren durchschnittlichen Bewegungsumfang im Vergleich zu Mädchen. Insgesamt deuten die Ergebnisse darauf hin, dass der Sportunterricht mit dem Inhalt Fußball einen substanziellen Beitrag zum täglichen Gesundheits- und Bewegungsverhalten leisten kann.

Thermal small steps staircase and layer migration in the Atlantis II Deep, Red Sea - Alaa M. A. Albarakati; Daniel F. McGinnis; Fazal Ahmad; Peter Linke; Marcus Dengler; Peter Feldens; Mark Schmidt; Radwan Al-Farawati (Arabian Journal of Geosciences, 2016)